Analisis Perputaran Persediaan Dalam Menilai Return On Asset (ROA) Pada PT. Kalbe Farma, Tbk Periode 2015 - 2019 - Edison Hamid (PARAMETER, 2021)
This study aims to determine how inventory turnover is in assessing Return On Asset. The research object, namely PT. Kalbe Farma, Tbk, which is taken from the financial reports for the period 2015-2019. This study used a qualitative method consisting of two variables, namely inventory cycle as the independent variable and return on asset the dependent variable. The data analysis method used in this research is inventory turnover analysis and return on asset analysis. The test results show that the average inventory turnover of 3.15 per year as a whole is categorized as good, when viewed from the general standard or the industry average which is above 2.5 times. For the average return on asset, it shows that return on asset is included in the very good criteria because it has reached the company standard. Then from the comparison of inventory turnover and return on assetor the last 5 years of the 2015-2019 period, the contribution of inventory turnover in assessing return on asset was 21.28% and the rest contributed to other factors not examined in this study. Penelitian ini bertujuan untuk mengetahui bagaimana perputaran persediaan dalam menilai Return On Asset. Objek penelitian yaitu PT. Kalbe Farma, Tbk yang diambil dari laporan keuangan periode 2015-2019. Penelitian ini menggunakan metode kualitatif yang terdiri dari dua variabel yaitu siklus persediaan sebagai variabel bebas dan return on asset sebagai variabel terikat. Metode analisis data yang digunakan dalam penelitian ini adalah analisis perputaran persediaan dan analisis return on asset. Hasil pengujian menunjukkan bahwa rata-rata perputaran persediaan 3,15 per tahun secara keseluruhan dikategorikan baik, jika dilihat dari standar umum atau rata-rata industri yang berada di atas 2,5 kali. Untuk rata-rata return on asset menunjukkan bahwa return on asset termasuk dalam kriteria sangat baik karena telah mencapai standar perusahaan. Kemudian dari perbandingan perputaran persediaan dan return on assetor 5 tahun terakhir periode 2015-2019, kontribusi perputaran persediaan dalam menilai return on asset adalah 21,28% dan sisanya berkontribusi pada faktor lain yang tidak diteliti dalam penelitian ini.